Focal boosted IMRT treatment of prostate cancer to 84 Gy in 28 fractions: preliminary clinical outcomes, toxicity, and dosimetry - Hands, Jacob Michael; Whalen, Michael J.; Haji-Momenian, Shawn; Frazier, Harold; Andrawis, Ramez; Provenzano, Destie; Bauman, Julie E.; Estephan, Fayez; Aghdam, Hamid; Chen, Dongjun; Goyal, Sharad; Ojong-Ntui, Martin; et al. (Frontiers in Oncology, 2025)
IntroductionThe FLAME trial reported that focal boosting of prostate tumors up to 95 Gy in 35 fractions improves biochemical control (disease-free survival). However, this treatment (regimen) is not commonly used in the United States. We investigated a focally boosted treatment of 84 Gy in 28 fractions (EQD2–108 Gy, BED 252 Gy).MethodsWe retrospectively evaluated men with unfavorable intermediate-risk (uIR) and high-risk (HR) prostate cancer treated with focal boost intensity-modulated radiotherapy (IMRT) between 2019 and 2022. The dose levels were 84 Gy to the gross tumor volume (GTV), 70 Gy to the prostate and proximal seminal vesicles, and an optional 50.4 Gy to elective pelvic lymph nodes (all 28 fractions). The treatment planning goal was to cover 95% of the GTV at 84 Gy, and also meet the target and normal tissue dosimetry criteria of the hypofractionated treatment arm of NRG-GU005. Volume-modulated arc therapy was used for treatment delivery. Androgen deprivation therapy (ADT) was given at the discretion of the treating physician.ResultsIn total, 20 men were included in the analysis, 2 (10%) with uIR and 18 (90%) with HR. Six (30%) tumors were GG2, three (15%) GG3, seven (30%) GG4, and four (20%) GG5. There were 13 (65%) stage cT1, 4 (20%) cT2, and 3 (15%) cT3 tumors. One (5%) patient received short-term ADT, 18 (95%) long-term ADT, and 1 (5%) refused ADT. Moreover, 18 (90%) men received elective pelvic nodal radiation. The mean baseline Prostate specific antigen (PSA) was 25.1 ng/mL (range 4.2–73.4). The median baseline International Prostate Symptom Score (IPSS) was 11.1 (IQR 4.5–12). Four patients had severe baseline urinary symptoms (IPSS ≥20). The mean baseline prostate volume was 57.4 cc (range 26.8–198.3). The mean volume of the 84 Gy boost target was 7.1 cc (range 2.3–15.0) and the mean proportion of the prostate boosted was 14.8% (range 2%–47%). Patients met all per-protocol normal tissue criteria of NRG-GU005, except for bladder D0.03cc, with a reported mean of 79.2 (≤73.5 Gy). At a median follow-up of 42 months (range 18–63), no patients had developed recurrence, metastasis, or death from prostate cancer. One patient died at 18 months from unrelated metastatic colorectal cancer. Acute grade 1–2 genitourinary (GU) toxicity occurred in 13 (65%) patients, and acute grade 1–2 gastrointestinal (GI) toxicity occurred in 4 (20%) patients. No patients developed grade 3+ acute or late GU or GI toxicity.ConclusionA novel 28-fraction focal boosted IMRT treatment is feasible and has an acceptable preliminary toxicity profile. Oncologic results are promising but require longer follow up and prospective study.